(untitled) (Global Journal of Science Frontier Research, 2018)
Nigera, the most populated country in Africa is faced with series of traffic congestions. This indisputable issue of traffic hold is occasioned by the growing population concentration, rapid urbanization, and increasing commercial and economic activities. High population generates heavy vehicular traffic, leading to vehicular conflict and congestion as well as other mobility related challenges, which adversely affect the ultimate goal of people’s mobility. The country is expected to offer high accessibility and mobility advantages, coupled with the provision of transportation infrastructures which are being threatened by mobility challenges resulting in low productivity and loss of man-hours within Nigeria, thus adversely affecting the overall wellbeing of residents.